Designing an intelligent system for genetic biology learning / S.Gangatharan Seenivasagam - S.Gangatharan, Seenivasagam (2001)
With the changing education scenario, an issue which has come strongly on how to create intelligent tutoring system to educate learners in a more intelligent way. So a need has emerged for the development of an intelligent tutoring system. This part or thesis describes the design of a collection of intelligent systems under the name GENETIC BIOLOGY for basic genetic biology tutoring. GENETIC BIOLOGY consist of three intelligent systems which arc designed for cell, DNA and gene learning. GENETIC BIOLOGY systems employ natural language processing and various techniques normally used in the construction of intelligent systems. Production rules and frames are widely used in representing knowledge of genetic biology.